The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1985
DOI: 10.1128/jb.162.2.529-534.1985
|View full text |Cite
|
Sign up to set email alerts
|

Recombination in recA cells between direct repeats of insertion element IS1

Abstract: The IS1 sequences that flank the Tn9 chloramphenicol acetyltransferase gene as direct repeats recombine after transformation into an Escherichia coli recA strain. The recombination requires the lambda pL promoter on the plasmid. A plasmid that contains mutant IS1 elements does not recombine. These results indicate that this recombination requires an IS1-specific gene product. The recombinational activity of IS1 may resolve transient cointegrates formed during the transposition of IS1. I discuss a possible role… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1988
1988
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…The analysis of the JE2571Rif r transconjugants surviving pAZAKT transfer showed that it was not due to the development of Zeta resistance. The survivors contained either an inactivated zeta gene or a recombinant of pAZAKT and the Epsilon-encoding plasmid from the donor, most probably due to the activity of chromosomally carried IS 1 ( 41 ).…”
Section: Discussionmentioning
confidence: 99%
“…The analysis of the JE2571Rif r transconjugants surviving pAZAKT transfer showed that it was not due to the development of Zeta resistance. The survivors contained either an inactivated zeta gene or a recombinant of pAZAKT and the Epsilon-encoding plasmid from the donor, most probably due to the activity of chromosomally carried IS 1 ( 41 ).…”
Section: Discussionmentioning
confidence: 99%